2018
DOI: 10.4172/2155-9600.1000712
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Traditional Vegetables in Japan: Physiological Function of Buckwheat Sprouts

Abstract: Sprouted buckwheat (germinated buckwheat seeds) has been traditionally used in the Tsugaru region of Japan. It has been consumed in the Aomori Prefecture, Tsugaru area, for over 350 years. As these buckwheat sprouts are technically the shoots of the plant, they offer several beneficial nutrients. Phytochemicals (metabolic products of plants), such as amino acids and polyphenols, are known to increase markedly upon seed germination. In recent years, attention to the worldwide slow-food orientation and low-glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…These values are in agreement with those presented by Yamanouchi et al [ 35 ], in which the mean value of antioxidant capacity of various plant samples was equal to 0.646 mM uric acid equivalents. This result is in agreement with several studies that demonstrated the higher antioxidant capacity of barley compared with other cereals [ 3 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These values are in agreement with those presented by Yamanouchi et al [ 35 ], in which the mean value of antioxidant capacity of various plant samples was equal to 0.646 mM uric acid equivalents. This result is in agreement with several studies that demonstrated the higher antioxidant capacity of barley compared with other cereals [ 3 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 93%
“…The highest TAC value (p < 0.001), expressed as mM uric acid equivalents, was observed in barley compared with wheat and corn, according to the highest phenolic content found that likely produced the stronger antioxidant capacity and an assortment of other bioactive phytochemicals [34]. These values are in agreement with those presented by Yamanouchi et al [35], in which the mean value of antioxidant capacity of various plant samples was equal to 0.646 mM uric acid equivalents. This result is in agreement with several studies that demonstrated the higher antioxidant capacity of barley compared with other cereals [3,36,37].…”
Section: Resultssupporting
confidence: 89%